An Initiative for the Study and Use of Genetic Diversity of Domesticated Plants and Their Wild Relatives - Mastretta-Yanes, Alicia; Acevedo Gasman, Francisca; Burgeff, Caroline; Cano Ramírez, Margarita; Piñero, Daniel; Sarukhán, José (Frontiers in Plant Science, 2018)
Domestication has been influenced by formal plant breeding since the onset of intensive agriculture and the Green Revolution. Despite providing food security for some regions, intensive agriculture has had substantial detrimental consequences for the environment and does not fulfill smallholder's needs under most developing countries conditions. Therefore, it is necessary to look for alternative plant production techniques, effective for each environmental, socio-cultural and economic conditions. This is particularly relevant for countries that are megadiverse and major centers of plant domestication and diversification. In this white paper, a Mexico-centered initiative is proposed, with two main objectives: (1) to study, understand, conserve, and sustainably use the genetic diversity of domesticated plants and their wild relatives, as well as the ongoing evolutionary processes that generate and maintain it; and (2) to strengthen food and forestry production in a socially fair and environmentally friendly way. To fulfill these objectives, the initiative focuses on the source of variability available for domestication (genetic diversity and functional genomics), the context in which domestication acts (breeding and production) and one of its main challenges (environmental change). Research on these components can be framed to target and connect both the theoretical understanding of the evolutionary processes, the practical aspects of conservation, and food and forestry production. The target, main challenges, problems to be faced and key research questions are presented for each component, followed by a roadmap for the consolidation of this proposal as a national initiative.